Digitizing Traditional Health in Indonesia Unlocks Community Potential - Badruli Martati; Ade Firmannandya; Pheni Cahya Kartika; Nur Mukarrohmah (Indonesian Journal of Cultural and Community Development, 2024)
This study addresses the digital gap in administration and marketing within traditional health practices, focusing on the asman as-shihah group in Jumputrejo Village. Traditional health practices like Family Medicine Gardens (TOGA) and acupressure are vital for community health but often lack digital integration.Employing a participatory approach with stages of preparation, implementation, and evaluation, we explored the adaptation of digital tools for administration and ICT for marketing. The program showed that digital skills significantly enhance the efficiency and reach of traditional health practices, suggesting that digital integration can promote sustainable community health initiatives. Future research should further investigate the long-term impacts of digitalization across other regions. Highlights: Digital Tools Boost Efficiency: Enhances administration and outreach. Community-Based Approach: Tailored, practical solutions. Sustainability: Digital adoption promotes long-term community health. Keywords: Digitalization, Traditional Health Practices, Community Health, ICT, Sustainable Development